Poesia e reflexividade na produção de três documentaristas brasileiros contemporâneos: Helena Solberg, Eduardo Coutinho e Walter Carvalho - Mariana Ribeiro da Silva Tavares (2006)
This work objectived to set up a dialogue among the reflexions os three brazilian movie makers Helena Solberg, Eduardo Coutinho and Walter Carvalho concerning the creation process in documentary making; to identify what they have in common and in what they diverge so that it makes possible for us to understand what is a documentary nowadays, its tendencies and its function; to analyse the creation procedures and the stylistic elements of some films made by the three movie makers mentioned above; to investigate the conditions which made it possible for the directors to review the relationship among the subjects treated in their films, questioning the conventions which have being developed throughout the twentieth century and turning the documentary into a laboratory of esthetics and content.